2006
DOI: 10.1590/s0034-71672006000700006
|View full text |Cite
|
Sign up to set email alerts
|

Ensino de Graduação em Enfermagem: a contribuição da Associação Brasileira de Enfermagem

Abstract: RESUMOO presente estudo apresenta algumas das ações mais relevantes da Associação Brasileira de Enfermagem para com o processo de formação da(o) enfermeira(o), no país, contextualizando essas ações com o momento histórico em que elas aconteceram. Nesse sentido, o estudo se constitui, não só, numa produção de conhecimento na área, mas também num elemento de registro da história do ensino de graduação em enfermagem no Brasil, oferecendo instrumentos de análise para a situação atual desse ensino. O texto destaca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…Analyzing the objects of study of the selected articles, it was found that, in the Brazilian context, ABEn was the focus of most of the studies, perhaps because it is the oldest nursing organization in the country, and even acts as an umbrella organization for other municipal, union, and scientific nursing organizations in Brazil (9,11,14) . It seems that, in a way, all of the articles addressed the contributions of the Association to the world of nursing, especially in the areas of education (15)(16) , care and professional practice (14,(17)(18) , political participation (19) , and preservation of the memory of the profession (13) . It is noteworthy that there was mention of unions, specialties, and supervisory bodies of professional nursing practice during the joint work developed by these institutions in favor of the demands of the field of nursing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing the objects of study of the selected articles, it was found that, in the Brazilian context, ABEn was the focus of most of the studies, perhaps because it is the oldest nursing organization in the country, and even acts as an umbrella organization for other municipal, union, and scientific nursing organizations in Brazil (9,11,14) . It seems that, in a way, all of the articles addressed the contributions of the Association to the world of nursing, especially in the areas of education (15)(16) , care and professional practice (14,(17)(18) , political participation (19) , and preservation of the memory of the profession (13) . It is noteworthy that there was mention of unions, specialties, and supervisory bodies of professional nursing practice during the joint work developed by these institutions in favor of the demands of the field of nursing.…”
Section: Discussionmentioning
confidence: 99%
“…As for the conclusions of the studies included in the present review, the evidence is that civil nursing organizations contribute to the development of the profession in its various areas of work (9)(10)(11)20) , in which professional training and care for human beings are the most discussed (15)(16)(17)(18)(21)(22)(23)(24) . In regard to professional practice and political participation in social movements, the need to strengthen and integrate such organizations is highlighted, along with the importance of participation of the working class in these associations (9)(10)(11)(12)19,20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the entity invested, and still invests, in the promotion of meetings, debate forums, workshops, as well as national and regional seminars, aiming to stimulate the participation of all those who are interested and involved in the nursing education area. 20 As Chair of the ABEn-SC, Ingrid was also indicated by the Federal Nursing Council to coordinate the commission that created the Regional Nursing Council of Santa Catarina (COREn-SC) in 1985.…”
Section: Methodsmentioning
confidence: 99%
“…(3,4) . Esse evento marca a exclusão do enfoque social e de saúde pública da grade curricular dos cursos de graduação em enfermagem e sua conseqüente associação com as ciências biológicas, com enfoque na especialização, priorizando uma prática operacional centrada no ambiente hospitalar, visando a cura do indivíduo, oriunda do modelo biomédico predominante na política de saúde do país (5,6) .…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified